Negative monetary policy rates and systemic banks' risk-taking: Evidence from the euro area securities register - Johannes Bubeck; Angela Maddaloni; José-Luis Peydró (Deutsche Bundesbank, 2020)
We show that negative monetary policy rates induce systemic banks to reach-for-yield. For identification, we exploit the introduction of negative deposit rates by the European Central Bank in June 2014 and a novel securities register for the 26 largest euro area banking groups. Banks with more customer deposits are negatively affected by negative rates, as they do not pass negative rates to retail customers, in turn investing more in securities, especially in those yielding higher returns. Effects are stronger for less capitalized banks, private sector (financial and non-financial) securities and dollar-denominated securities. Affected banks also take higher risk in loans.
Keywords: E43; E52; E58; G01; G21; 330; Negative Rates; Non-Standard Monetary Policy; Reach-for-Yield; Securities; Banks